New Results on Bandwidth of GaAs PIN Photodiodes - M. A. Grado Caffaro; M. Grado Caffaro (Active and Passive Electronic Components)
In this paper an equivalent circuit of a GaAs PIN photodiode for the millimeter wave range is proposed. Moreover, an approximate expression for the bandwidth of this circuit is obtained. By using the effective quality factor concept, an equation that includes the value of a hypothetical resistance involved in the circuit mentioned above, is derived. In the context of fiber optic communications, this "resistance" represents the losses due to the fiber-photodiode coupling.